Students, the Photographer and the History: Meeting in Bahia, 1979 (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The article analyses the independent photographic coverage of the photojournalist Milton Guran, during the XXXI Congress of UNE, that happened in Salvador, Bahia, in 1979 and this main result, the photo book: “Encontro na Bahia 79”. The study is based upon the reflections of the Italian philosopher Giorgio Agamben, in which photography is shaped as gesture of commitment to the cause of resistance to the military regime and to the fight for civil rights in Brazil. Oral history methodology sustains the work of reconstruction of the historical memory of the XXXI Congress of UNE, focusing on the year of 1979, intertwining words and images of the event with press news produced at this period and complementary documentation.
Keywords: Milton Guran; Photography; Students’ Movement; Military Dictatorship.